Clinical effect of photodynamic therapy on primary carious dentin after partial caries removal - Pierre Adriano Moreno NEVES; Leonardo Abrantes LIMA; Fernanda Cristina Nogueira RODRIGUES; Tarcisio Jorge LEITÃO; Cecília Cláudia Costa RIBEIRO (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract This study was conducted to assess the clinical effect of photodynamic therapy (PDT) in the decontamination of the deep dentin of deciduous molars submitted to partial removal of carious tissue. After cavity preparation, dentin samples were taken from the pulp wall of nineteen deciduous molars before and after PDT application. Remaining dentin was treated with 0.01% methylene blue dye followed by irradiation with an InGaAlP diode laser (λ - 660 nm; 40 mW; 120 J/cm2; 120 s). Dentin samples were microbiologically assessed for the enumeration of total microorganisms, Lactobacillus spp. and mutans streptococci. There was no significant difference in the number of colony-forming units (CFU) for any of the microorganisms assessed (p > 0.05). Photodynamic therapy, using 0.01% methylene blue dye at a dosimetry of 120 J/cm2 would not be a viable clinical alternative to reduce bacterial contamination in deep dentin.